phonemic awareness: language-specific and universal contributions - Barnes, Emily; Ni Chiarain, Neasa (My University, 2024)
This paper examines the construct of bilingual phonemic awareness in Irish-English bilinguals. Though traditionally viewed as a skill or ability which transfers across languages, recent accounts have considered whether phonemic awareness has a language-specific component. This study used a cross-sectional design to examine this question. A total of 345 students in Irish immersion schools and in schools in Gaeltacht (Irish-speaking) areas took part in the study and were administered Phoneme Deletion and Phoneme Matching in both Irish and English. Results demonstrate (i) a low correlation between Phoneme Matching and Phoneme Deletion scores within each language (ii) a significant difference between Phoneme Matching scores in Irish and English, but no significant difference in Phoneme Deletion scores in each language (iii) that orthographic representations influence performance on Phoneme Matching tasks in both Irish and English, and (iv) that participants demonstrate a low level of accuracy on velarised-palatalised phonemic contrasts, which are specific to Irish. Overall, this paper concludes that bilingual phonemic awareness is a multidimensional – rather than a unitary – construct. It has both a metalinguistic and epilinguistic component, and is likely influenced by linguistic, sociolinguistic and educational factors. The practical implications for dual-language education are discussed.
PUBLISHED
Keywords: Bilingual phonemic awareness; Phonological awareness; Early literacy; Immersion education